Democracia das vozes do discurso: a percepção do feminismo na voz de uma mulher jornalista e escritora - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The present work approaches feminism from the point of view of the American journalist and writer Rebecca Solnit, as manifested in two of her literary works of non-fiction published in Brazil. Through the journalist's perspective, it was possible to discuss the pluralization of the term feminism into feminisms. The research also made it possible to criticize the feminist movement, without inferiorizing it, criticizing the flaws of feminism that promoted the segmentation of the movement into several strands - because the whole did not contemplate all types of being a woman -, and pointing out the relevance of feminisms even nowadays, with gender violence still being a problem in the national scenario and beyond. With textual and discourse analysis, through biographical and bibliographical research, we understand that the media contributed both to stigmatizing the feminist movement, and also served as a stage to amplify Rebecca Solnit's voice, which reached so many other people, discussing not only gender, but diversity in general. This paper discussed gender, diversity, literary journalism, journalistic sensibility and subjectivity, politics, and discourse.
Keywords: Feminismo; Jornalismo; Identidade de gênero; Solnit, Rebecca; Feminism; Journalism; CNPQ::CIENCIAS SOCIAIS APLICADAS